Gambaran Perilaku Pencarian Pengobatan Penderita Demam Berdarah Dengue di Kabupaten Ciamis Propinsi Jawa Barat - Rohmansyah Wahyu Nurindra; Imas Masturoh; Joni Hendri; Mara Ipa (Loka Litbang Kesehatan Pangandaran, 2010)
A cross sectional study was carried out to determine health seeking behaviour of dengue patient in Ciamis district. Subjects were 80 dengue patient’s care taker chosen by purposive sampling. Data was presented descriptively.The result showed based on the first place of treatment, pattern of treatment seeking behavior were identified the most commonone was using public hospital as the first step. Pattern of treatment seeking behavior of the patient’s care taker that influenced decision making to take treatment alternatives included knowledge, attitude and practice about the caused, symptomp’s, virulence and transmissionof dengue virus infection; the distance to treatment places and family role (husband/wife) were important for caretakers to take into consideration when making treatment choices.